Kejadian Tuberkulosis Paru di Wilayah Kerja Puskesmas Driyorejo Dipengaruhi oleh Sanitasi Rumah - Milanti Nadia Fitri; Pratiwi Hermiyanti; Khambali Khambali; Setiawan Setiawan; Marlik Marlik (FORIKES, 2022)
The control of pulmonary tuberculosis is still a national program and pulmonary tuberculosis is ranked third at the Driyorejo Health Center. The aim of the study was to determine the relationship between home sanitation and the incidence of pulmonary tuberculosis in the Driyorejo Public Health Center Work Area. The design of this research was case-control. The variables studied were the type of floor, wall, ventilation, lighting, humidity, temperature, occupancy density, kitchen smoke vents and the incidence of pulmonary tuberculosis. The population was 84 houses, the control and case sample sizes were 38 houses each. Data were analyzed by Chi-square test. The results of the analysis showed that there was a relationship between the incidence of pulmonary tuberculosis with ventilation area (p = 0.021), lighting (p = 0.021), humidity (p = 0.021), temperature (p = 0.038), occupancy density (p = 0.012), smoke vents kitchen (p = 0.003) and home sanitation (p = 0.01). Furthermore, it was concluded that home sanitation was associated with the incidence of pulmonary tuberculosis.Keywords: pulmonary tuberculosis; home sanitation ABSTRAK Penanggulangan tuberkulosis paru masih menjadi program nasional dan tuberkulosis paru masuk peringkat ketiga di Puskesmas Driyorejo. Penelitian bertujuan untuk mengetahui hubungan antara sanitasi rumah dengan kejadian tuberkulosis paru di Wilayah Kerja Puskesmas Driyorejo. Rancangan penelitian ini adalah case-control. Variabel yang diteliti adalah jenis lantai, dinding, ventilasi, pencahayaan, kelembaban, suhu, kepadatan hunian, lubang asap dapur dan kejadian tuberkulosis paru. Populasi sebanyak 84 rumah, ukuran sampel kontrol dan kasus masing-masing adalah 38 rumah. Data dianalisis dengan uji Chi-square. Hasil analisis menunjukkan bahwa ada hubungan antara kejadian tuberkulosis paru dengan luas ventilasi (p = 0,021), pencahayaan (p = 0,021), kelembaban (p = 0,021), suhu (p = 0,038), kepadatan hunian (p = 0,012), lubang asap dapur (p = 0,003) dan sanitasi rumah (p = 0,01). Selanjutnya disimpulkan bahwa sanitasi rumah berhubungan dengan kejadian tuberkulosis paru.Kata kunci: tuberkulosis paru; sanitasi rumah